2012
DOI: 10.1038/gt.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

Effector memory and central memory NY-ESO-1-specific re-directed T cells for treatment of multiple myeloma

Abstract: The cancer-testis antigen NY-ESO-1 is a potential target antigen for immune therapy expressed in a subset of patients with multiple myeloma. We generated chimeric antigen receptors (CARs) recognizing the immunodominant NY-ESO-1 peptide 157-165 in the context of HLA-A*02:01 to re-direct autologous CD8(+) T cells towards NY-ESO-1(+) myeloma cells. These re-directed T cells specifically lysed NY-ESO-1(157-165)/HLA-A*02:01-positive cells and secreted IFNγ. A total of 40% of CCR7(-) re-directed T cells had an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 46 publications
3
58
0
Order By: Relevance
“…4,8 In myeloma, a multitude of studies have investigated MM-associated antigens, yielding a handful of promising targets. [25][26][27][28][29][30][31][32][33][34][35] However, these studies were limited in scope of antigens and HLA allotypes. 42 In our previous studies in acute myeloid leukemia and chronic lymphocytic leukemia, we demonstrated that the comprehensive and comparative analysis of the HLA-presented antigenome can identify extensive panels of broadly presented T-cell epitopes covering a multitude of HLA allotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8 In myeloma, a multitude of studies have investigated MM-associated antigens, yielding a handful of promising targets. [25][26][27][28][29][30][31][32][33][34][35] However, these studies were limited in scope of antigens and HLA allotypes. 42 In our previous studies in acute myeloid leukemia and chronic lymphocytic leukemia, we demonstrated that the comprehensive and comparative analysis of the HLA-presented antigenome can identify extensive panels of broadly presented T-cell epitopes covering a multitude of HLA allotypes.…”
Section: Discussionmentioning
confidence: 99%
“…24 An array of myeloma-associated T-cell antigens has been described in previous studies. [25][26][27][28][29][30][31][32][33][34][35] Most of these antigens were identified based on gene expression analysis and reverse immunology. Some of these antigens (WT1, 36,37 RHAMM, 38,39 hTERT, 40 and Survivin 40,41 ) have already found their way into clinical trials, showing promising results in terms of induction of specific T-cell responses as well as clinical responses in single patients.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, the first successful study had demonstrated that transfer of an HLA-A2-restricted MART-1 antigen-specific TCR into human T cells could confer them the specificity toward malignant melanomas [14]. Several preclinical and clinical studies have also exhibited that genetic modification with a tumor antigen-specific TCR could yield an antigen-specific T cell population [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Novel therapies like bi-specific antibodies are demonstrating early clinical success, 27,28 and methods that bypass the endogenous immune system, such as genetically-engineered T cells, have also drawn a great deal of attention for the successes demonstrated using chimeric antigen receptors. 2,8,9,29 While several adult cancer have been evaluated for NY-ESO-1 expression and its ability to serve as an immunotherapeutic target, 15,16,30 pediatric cancers have been largely overlooked. A trial targeting NY-ESO-1 C synovial cell carcinoma using the T cells investigated in this report is currently enrolling; however, this clinical trial is, to our knowledge, the only such pediatric trial targeting NY-ESO-1 (Clinicaltrials.gov Identifier NCT01343043).…”
Section: Discussionmentioning
confidence: 99%